Treatment of Cardiogenic Shock and Refractory Ventricular Fibrillation: Pulling Out All the Stops - Glazier, Margaret Mary; Kaki, Amir (International Journal of Angiology, 2023)
We report the case of a 62-year-old woman who presented with an acute inferior wall myocardial infarction complicated by cardiogenic shock and refractory ventricular fibrillation. Following prolonged resuscitation in the emergency room, she was transferred to the cardiac catheterization laboratory where, as a first step, mechanical circulatory support with venoarterial extracorporeal membrane oxygenation (ECMO) was established. Next, a right heart catheterization study was performed, followed by coronary angiography and angioplasty of the infarct-related artery. Promptly on transfer to the intensive care unit, a hypothermia protocol was initiated. By postprocedure day 1, the patient's ventricular fibrillation had resolved, mean arterial pressure was >65 mm Hg, and pulmonary artery diastolic pressure was 10 mm Hg. Echocardiography demonstrated complete recovery of left ventricular systolic function. Lactate levels had fallen from 11.0 mmol/L (pre-ECMO) to 1.2 mmol/L. The patient was successfully weaned off pressor and ECMO support within 24 hours of the percutaneous coronary intervention procedure. She was extubated on postprocedure day 2 and discharged home on day 6. At 26-month follow-up, she remains well, angina free, neurologically intact, and without evidence of heart failure. The treatment algorithm used in this case should be considered favorably in the management of patients presenting with acute myocardial infarction complicated by cardiogenic shock and refractory ventricular fibrillation.
Keywords: ventricular fibrillation; ECMO; angioplasty; right heart catheterization; acute myocardial infarction; coronary artery; cardiogenic shock